Noninvasive Follicular Thyroid Neoplasm with Papillary-like Nuclear Features (NIFTP): Tumour Entity with a Short History. A Review on Challenges in Our Microscopes, Molecular and Ultrasonographic Profile - Ivana Kholová; Elina Haaga; Jaroslav Ludvik; David Kalfert; Marie Ludvikova (Diagnostics, 2022)
Since Noninvasive Follicular Thyroid Neoplasm with Papillary-like Nuclear Features (NIFTP) was introduced as a new thyroid tumour entity, many studies, and meta-analyses on diagnosing NIFTP have been published. NIFTP-revised histopathological criteria emerged in 2018. NIFTP is defined as a histological entity and its diagnosis requires a careful histological examination. Its molecular profile is similar to follicular-like tumours. Ultrasound features are unable to differentiate NIFTP. NIFTP is not a cytological diagnosis, but it influences the risk of malignancy in several categories of The Bethesda System for Reporting Thyroid Cytopathology terminology.